2010
DOI: 10.1007/s00421-010-1586-4
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity interval training improves VO2peak, maximal lactate accumulation, time trial and competition performance in 9–11-year-old swimmers

Abstract: Training volume in swimming is usually very high when compared to the relatively short competition time. High-intensity interval training (HIIT) has been demonstrated to improve performance in a relatively short training period. The main purpose of the present study was to examine the effects of a 5-week HIIT versus high-volume training (HVT) in 9–11-year-old swimmers on competition performance, 100 and 2,000 m time (T100 m and T2,000 m), VO2peak and rate of maximal lactate accumulation (Lacmax). In a 5-week c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
3
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(122 citation statements)
references
References 20 publications
7
95
3
6
Order By: Relevance
“…Thus, a natural plateau in VO 2max may have been reached prior to the initiation of the study. This suggestion is somewhat supported by the observation that HIT induces similar increases in VO 2max as low-intensity high-volume training in young swimmers aged ∼10 years [19] as well as in adult swimmers when preceded by a four months break [20]. It may also be considered that swimming VO 2max may not have been limited by the central cardiovascular capacity as expected during running or cycling [30] but more so by the upper body capacity to extract oxygen.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, a natural plateau in VO 2max may have been reached prior to the initiation of the study. This suggestion is somewhat supported by the observation that HIT induces similar increases in VO 2max as low-intensity high-volume training in young swimmers aged ∼10 years [19] as well as in adult swimmers when preceded by a four months break [20]. It may also be considered that swimming VO 2max may not have been limited by the central cardiovascular capacity as expected during running or cycling [30] but more so by the upper body capacity to extract oxygen.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, individuals with a variety of diseases, including children (Engel et al, 2014;Sperlich et al, 2011;Sperlich et al, 2010), subjected to high-, rather than low-intensity exercise (Elliott, Rajopadhyaya, Bentley, Beltrame, & Aromataris, 2014;Gielen, Laughlin, O'Conner, & Duncker, 2015;Kessler, Sisson, & Short, 2012;Little & Francois, 2014) have experienced no negative consequences for health. In fact, an acute session of high-intensity cycling was recently reported to improve selective attention and short-term memory in middle-aged adults (Alves et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The level of physical activity during organized youth sports practices varies substantially and in 7–14‐year‐old children, football is associated with comparatively higher activity than e.g., baseball/softball (Leek et al., ). In this regard, it is notable that recent data have suggested that high‐intensity interval training (HIIT) may be more effective than low‐to‐moderate‐intensity training for improving fitness and cardiac function than moderate‐intensity training in children and adolescents (Tjønna et al., ; Ingul et al., ; Sperlich et al., ; Buchan et al., ). In line with these findings, we recently observed that 9–10‐year‐old school children had marked improvement in aerobic fitness after only 6 weeks with two 30‐min high‐intensity football and unihockey training sessions per week (Bendiksen et al., ).…”
mentioning
confidence: 99%